Lunisolar tidal synchronism with biophoton emission during intercontinental wheat-seedling germination tests - Gallep, Cristiano M; Moraes, Thiago A; Cervinková, Kateřina; Cifra, Michal; Katsumata, Masakazu; Barlow, Peter W (Plant signaling & behavior, 2014)
Synchronic measurements of spontaneous ultra-weak light emission from germinating wheat seedlings both in Brazil and after transportation to Japan, and with a simultaneous series of germinations with local seedlings in the Czech Republic, are presented. A series of tests was also performed with samples returned from Japan to Brazil and results compared with those from undisturbed Brazilian seedlings. Native seedlings presented semi-circadian rhythms of emission which correlated with the gravimetric tidal acceleration at their locality, as did seeds which had been transported from Brazil to Japan, and then returned to Brazil. Here, however, there were very small disturbances within the periodicity of emissions, perhaps as a result of similar tidal profiles at locations whose longitudes are 180° apart, as in this case, different from previous results obtained in Brazil-Germany tests with other longitude shift. This feature of the Brazil and Japan locations may have minimized the requirement for the acclimatization of the transported seed to their new location.
Keywords: cestování letadlem; Triticum; chronobiology; klíčení; germination; Circadian Rhythm; cirkadiánní rytmus; biophoton emission; gravimetric tides; Gravitation; semenáček; Seedlings; Photons; Germination; gravitace; pšenice; Air Travel; fotony